Biosynthesis of selenium-modified tRNAs in Methanococcus vannielii. - Politino, M (1990)
Selenium-containing nucleosides are natural components of several tRNA species in Methanococcus vannielii. In the present study, the incorporation of selenium from 75SeO3(2-) into these macromolecules was investigated in sonic extracts of M. vannielii. Nucleoside analysis of the 75Se-labeled tRNAs from these in vitro reaction mixtures demonstrated that the selenium was present in 75Se-labeled nucleosides identical to the two naturally occurring 2-selenouridines produced in vivo. Incorporation of selenium into these nucleosides was ATP-dependent and was maximal after 20 min. Addition of O-acetylserine enhanced the activity 2- to 3-fold, implicating a role for selenocysteine in the reaction. Added L-selenocysteine could function as a selenium donor, but the D isomer and DL-selenomethionine were inactive. RPC-5 chromatography of bulk tRNA isolated from M. vannielii grown on 75SeO3(2-) separated five major species of seleno-tRNAs. The amino acid-accepting activity of these tRNAs was investigated.